The Concept of Husnul Khotimah in the Syiir of Erang-erang Sekar Panjang by Charismatic NU Kyai Named Muhammad Siraj: A Study of Hermeneutics - Ithafur Rahman (Lakpesdam PCNU Kota Salatiga, 2021)
Syiir Erang-erang Sekar Panjang was written by a charismatic NU kyai named K.H. Muhammad Siraj Payaman Magelang. Writing poetry is like an expression full of meaning and bound to the conventions of old poetry. However, on the other hand there is leeway to play with the convention. The theory to explore the meaning of this poem is the phenomeological hermeneutics theory. The phenomenological approach tries to open meaning from lingua interpretation to philosophical interpretation. The method used in this research is the dialectical method. The working mechanism of dialectics consists of thesis, antithesis, and synthesis. The results of this study indicate that Syiir Erang-erang Sekar Panjang contains a deep philosophical meaning related to death, namely the deconstruction of lay views regarding death. This verse states that death is only an effect of life and is precisely the beginning of the next life, namely life in the grave and the hereafter. In addition, the concept of husnul khotimah is also found in this syiir which consists of recommendations and prohibitions. There are six recommendations in this syiir, namely nrima, loma, food gathering, performing fardhu prayers, obedience and repentance, and always remembering death. There are five prohibitions contained in this verse, namely the prohibition of excessive love of the world, the prohibition of predicting the world, the prohibition of always feeling lacking, the prohibition of ambition to seek the world, and the prohibition of accumulating wealth.